Residual Stress Analysis of Steel Fibre Reinforced Composite Inverted-Tooth Chains - Solmaz, Murat Yavuz (Carl Hanser Verlag, 2012)
The aim of this study is to investigate effects on the residual stresses of the fibre orientations and stacking sequences of the inverted-tooth chains which are made of transversely reinforced steel fibre thermoplastic laminated composite materials. For this purpose, fifteen different tooth chain models were created and stress analysis was performed with ANSYS 11.0 finite element program. For each fibre orientation and stacking sequence values of the yield loads where yielding of the inverted-tooth chain just initiates were determined. Then, loads subjected to the inverted-tooth chains were incrementally increased beyond the yield limits to determine plastic and residual stresses that were obtained by removing applied loads from the inverted-tooth chain. As a result of the analysis, it was observed that all values of residual stress components increased depending on the rising applied loads for all fibre orientation as well as for all stacking sequences.
Keywords: Load; Plates